Perennial Gardening in Florida - Sydney Park Brown (EDIS)
Revised! ENH-68, an 11-page fact sheet by Sydney Park Brown, describes herbaceous plants that, once established, can become a more permanent part of the landscape -- selection and use, planting and care, propagation, and pests and diseases. Includes a 7-page table of useful information for selecting and growing flowering perennials in Florida. Published by the UF Department of Environmental Horticulture, February 2007.